Chemical modification of carbon fiber with diethylenetriaminepentaacetic acid/halloysite nanotube as a multifunctional interfacial reinforcement for silicone resin composites. (6th November 2019) - Zheng, Yawen; Wang, Xiaoyun; Wu, Guangshun
Abstract : In the present research, a multifunctional hierarchical reinforcement was prepared by chemical modification of carbon fibers (CFs) with halloysite nanotubes (HNTs) by the bridging diethylenetriaminepentaacetic acid (DTPA) for improving interfacial microstructures and properties of composites. Surface structures and groups of modified HNTs and CFs were characterized systematically. The uniform distributions of the introduced DTPA and HNTs helped to increase fiber polarity, surface energy, and wettability. As a consequence, significant enhancements of interfacial properties and hydrothermal aging resistance of composites were achieved, and interfacial reinforcing mechanisms have also been studied. Moreover, the storage modulus showed a 17.95% improvement, and the glass transition temperature was enhanced by 17°C by dynamic mechanical analysis testing.